Nucleic Acids as Molecular Diagnostics. - Keller, Andreas (Wiley-VCH, 2014)
By integrating technology, supporting infrastructure and efficient application, this all-in-one guide presents molecular diagnostics as an essential component of modern, personalized clinical practice. It considers all important aspects, from the hardware and software needed, to recent improvements in blood- and non-blood-based biomarker tests. Chapters on ethical challenges and a look at current trends and the latest innovations are also included.Bridging the gap between industry and academia, this is a highly useful resource for practitioners as well as for developers of modern, DNA- and RNA.